(untitled) (قضايا سياسية, 2022)
This study aims to identify the Ottoman state’s position from the religious reform movement that happened in some of the German emirates in the year 1517 AD, until the signing of the Augsburg Peace agreement in 1555, and how it was deployed to serve its security purposes. The researcher used many resources and references to study different aspects of the subject to serve the whole study, Utilizing the authentic inquire about strategy based on displaying the authentic story and attempting to explain its occasions to make the objective system of the ponder, the setting of which came beginning with the components affecting the direction of Ottoman state’s Foreign Policy, outside approach, and after that investigating the part of the Catholic Church within the rise of Martin Luther’s identity and his change demands, and after that the clarity of the state’s position and clarifying its objectives of attempting to bolster the devout change development, and appearing the viewpoints of the Protestant- Ottoman rapprochement. The matter which empowered the researcher to reach a few comes about, counting: the victory of the Footrest intercession approach in accomplishing its security interface, and empowering the devout change development to fortify its faithfulness within the confront of majestic military impact and ecclesiastical devout impact, which driven to the foundation of its nearness in Europe.